Strategies for the formalization of MYPES in the services sector in Peru and the collection of IGV - Manco Petreucic, Ayar Lee (mktDESCUBRE, 2024)
The objective of this article is to analyze the strategies for the formalization of micro and small businesses (MYPES) ​​in the services sector and the collection of the general sales tax in Peru. The research approach is quantitative, descriptive scope and non-experimental transectional design. The sample was made up of 135 workers from MYPES companies in the district of Villa el Salvador dedicated to the provision of services. The survey was used as a data collection technique and the rating scale questionnaire was used as an instrument. The study concludes by highlighting key strategies such as tax education, the simplification of administrative processes and access to financial resources, which are essential to promote the formalization of MYPES in the services sector of the district of Villa el Salvador and improve VAT collection. in Peru.